Big Book Media to Reduce Early Childhood Children's Picky Eating Habits - Maghfiroh; Muhtarom; Dewi S, Anita Chandra (Journal of Education Reseach and Evaluation, 2025)
Picky eating is characterised by a child's tendency to reject certain types of food, which impacts nutritional adequacy, growth disorders, and physical and cognitive development of children. This type of research is development (R&D) using the ADDIE model. The research subjects included material experts, media experts, and nutritionists. The subjects of this trial or research and development were group B, with a total of 36 children. The data collection method used questionnaires, interviews, observations, and documentation. The instrument used in collecting data was a questionnaire sheet. The data analysis techniques used were qualitative, quantitative descriptive analysis, and inferential statistics. The validation results showed that the assessment results from learning material experts were 96% (very good), learning media experts 97% (very good), and nutritionists 95% (very good), so that the media was suitable for use in learning. The trial results showed an increase in the average score from the pretest of 60 to the posttest of 81.89, or an increase of about 36.5%. Statistical analysis using the Wilcoxon Signed Rank Test obtained an Asymp. Sig. Value. (2-tailed) = 0.001 < 0.05, which means there is a significant difference between the pretest and posttest. It is concluded that the Big Book media is valid, practical, and effective as a fun nutritional education tool to reduce picky eating habits in early childhood, as well as being a reference for teachers and parents in supporting children's healthy eating patterns.